Selenium-enriched yeast reduces caecal pathological injuries and intervenes changes of the diversity of caecal microbiota caused by Ochratoxin-A in broilers. (March 2020) - Yang, Shuhua; Li, Lin; Yu, Lihui; Sun, Lin; Li, Kang; Tong, Cui; Xu, Weixiang; Cui, Gengyuan; Long, Miao; Li, Peng
Abstract: We investigated the protective effect and mechanism of selenium-enriched yeast (SY) on caecal injury induced by ochratoxin A (OTA) in broilers. Eighty broiler chickens of 1-day-old with similar weight were randomly assigned to Control group, OTA group, SY group and OTA + SY group, and were intragastricaly administered with OTA and SY for 21 consecutive days. The results showed that SY could reduce the caecal pathological injuries and could inhibit oxidative stress caused by OTA exposure. The OTA + SY group showed a statistically significant ( p < 0.01) reduction in the level of MDA, IL-1β, IL-6 and IFN-γ, whereas the levels of GSH, SOD activity and IL-10 were significantly increased ( p < 0.01). By regulating TLR4/MYD88 signaling pathway, SY inhibited the expression of NF-κB, increased the expression of tight junction-related genes Claudin-1, Occludin and ZO-1, and antagonized the intestinal barrier injury caused by OTA exposure. Moreover, the microbial diversity analyses indicated that SY could intervene changes in the diversity of gut microbiota and the imbalance of gut microbiota caused by OTA. SY could relieve caecal pathological injuries, alleviate OTA-induced caecal oxidative stress and inflammatory response, increase the gut microbial diversity and protect broiler's intestinal barrier from injury.